2009
DOI: 10.1097/bcr.0b013e3181a289a6
|View full text |Cite
|
Sign up to set email alerts
|

A Case-Matched Controlled Study on High-Voltage Electrical Injuries vs Thermal Burns

Abstract: The aim of this study was to provide an increased level of evidence on surgical management of high-tension electrical injuries compared with thermal burns using a case-controlled study design. Sixty-eight patients (64 males, 4 females, aged 33.7 +/- 13 years) with high-tension electrical burns were matched for age, gender, and burnt extent with a cohort of patients sustaining thermal burns. Data were analyzed for cause of accident (occupational vs nonoccupational), concomitant injuries, extent of burn and burn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 25 publications
0
35
0
6
Order By: Relevance
“…Handschin et al[19] reported average 44 d of hospital stay and Noble et al[1] in their study reported hospital stay 24.5 ± 21 d in electrical injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Handschin et al[19] reported average 44 d of hospital stay and Noble et al[1] in their study reported hospital stay 24.5 ± 21 d in electrical injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Many cases of HVEI to the upper arms inevitably lead to amputation because the massively destroyed vessel walls easily undergo coagulation necrosis, leading to thrombosis and local obstruction of blood flow. The distal ends of the injured limbs may then become gangrenous [5,14]. …”
Section: Discussionmentioning
confidence: 99%
“…Usually, HVEI is associated with entry and exit wounds, and assessment of the pathway allows prediction of the organs at most risk of damage [2]. In HVEI, nearly 90% of victims have injuries in their upper extremities [3,4], with amputation required in 24% to 49% of cases [5,6]. The extent of the injury depends on the electrical voltage, the local tissue resistance, the pathway of the current flow, and the duration of the contact [7].…”
Section: Introductionmentioning
confidence: 99%
“…Fascial flaps (3), preexpanded flaps (4,5), composite tissue flaps, multiple flap transplantations in the same patient and combined flaps (‘chimeric’ flaps) based on a single pedicle have been performed in patients with severe burns and high‐voltage injuries (6). However, the risk of flap failure in high‐voltage injuries ranges between 10% and 30% because of microvascular damage by the electrical current (7–9). Therefore alternative techniques for reconstruction have to be kept in mind.…”
Section: Introductionmentioning
confidence: 99%